ICT integration in teaching and learning: perceptions and practices of secondary school students in Tanzania - Daudi, Yusuf; Nzilano, Lameck (University of Dar es Salaam Library Journal, 2020)
The study examined perceptions and practices of students regarding the use of Information and Communication Technology (ICT) in teaching and learning at a public secondary school in Ilala district in Tanzania. Specifically, the study focused on assessing secondary school students ' ICT related knowledge and skills in Ilala district, finding out how secondary school students in Ilala district use ICT facilities in learning, and gathering opinions and views of secondary school students in Ilala district on ICT integration in teaching and learning. The study used a combination of qualitative and quantitative approaches under a case study design to gather data through focus group discussion (FGD) and questionnaire survey methods from students at the respective school. The study involved twenty five (25) students selected through simple random sampling, who were provided with a questionnaire to respond to, and ten (10) FGD participants purposively selected. The study used thematic and descriptive techniques to process qualitative and quantitative data respectively. The study findings have revealed positive students ' perception towards ICT integration in teaching and learning. The students have also demonstrated to have knowledge and skills for using different ICT tools including desktop computers, laptops, Smartphones, Smart boards and iPads. However, the students reported to be provided with insufficient time to spend on computer programmes, they were banned from bringing personal ICT devices to school and that ICT devices usage was only limited to learning computer course instead of being used in all subjects. The study recommends that the secondary school administration should change unfriendly rules, which limit students from using personal ICT facilities in teaching and learning. ICT user education should be provided to public schools in response to the negative mind set on students ' use of ICT for learning.